THE INFLUENCE OF WORK SHIFTS AND WORK FACILITIES ON EMPLOYEE PERFORMANCE AT PT INDOBEST ARTHA KREASI - Maulana, Reza (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
To optimize Employee Performance, all resources need to be managed optimally including Work Shifts as a work system and Work Facilities. With good resource management, of course, companies can optimize the performance of their employees to maximize company performance. The purpose of this study was to determine the effect of Work Shifts and Work Facilities on Employee Performance partially or simultaneously. The research method used is quantitative method so that the direction and magnitude of the influence of exogenous variables on endogenous variables can be clearly described. The research data used primary data with a sample size of 70 employees at PT Indobest Artha Kreasi. The sampling method taken using nonprobablity sampling using saturated samel technique and using a questionnaire instrument for data collection. The results showed that: 1). Work Shift has a significant effect on Employee Performance, 2). Work Facilities have a significant effect on Employee Performance, 3). Work Shift and Work Facilities simultaneously have a significant effect on Employee Performance. The research implication shows that there is an influence of Work Shift and Work Facilities on Employee Performance.